The role of information systems in monitoring and evaluating green economy policies in Indonesia - Chakim Annubaha (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2025)
Background: Digital transformation in national development governance has become a critical enabler of Indonesia’s green economy agenda. The Ministry of National Development Planning (Bappenas) has developed two key digital systems, KRISNA and e-Monev, to support evidence-based monitoring and evaluation (M&E). This study examines the effectiveness and integration of these systems in monitoring low-carbon development programs during the 2020–2024 period. Methods: This research employs a descriptive-analytical approach combining qualitative and semi-quantitative methods, using secondary data from official reports of Bappenas, the Ministry of Environment and Forestry, UNDP, OECD, and relevant international literature published between 2020 and 2025. The analysis applies the Information Systems Success Model and the Digital Governance Framework to assess system quality, information quality, and policy impact. Finding: The findings indicate that the integration of KRISNA and e-Monev has improved transparency, efficiency, and consistency in reporting green development outcomes. By 2024, approximately 78% of more than 2,300 low-carbon development programs had been integrated across ministries and agencies, enabling more coordinated monitoring. Key performance indicators show a 24.7% reduction in greenhouse gas emission intensity from the 2010 baseline and an increase in the renewable energy share to 14.8% in 2023. Overall system effectiveness achieved a high average score of 4.22 out of 5, with information quality and policy impact rated strongest, while challenges remain in inter-agency data interoperability, particularly at the sub-national level. Conclusion: These findings demonstrate that digital M&E functions not only as a technocratic tool but also as a policy learning mechanism that enhances governmental adaptability to sustainable development goals and strengthens policy coherence in green economy governance. Novelty/Originality of this article: This study advances digital governance and green policy M&E literature by demonstrating how integrated national digital systems improve policy coherence and monitoring performance, while offering recommendations to enhance interoperability and data integration.